Polarimetric measurements in prominences and "tornadoes" observed by THEMIS. Issue Volume 10:Issue S305(2014) (24th July 2015) - Schmieder, Brigitte; Ariste, Arturo López; Levens, Peter; Labrosse, Nicolas; Dalmasse, Kévin
Abstract: Since 2013, coordinated campaigns with the THEMIS spectropolarimeter in Tenerife and other instruments (space based: Hinode/SOT, IRIS or ground based: Sac Peak, Meudon) are organized to observe prominences. THEMIS records spectropolarimetry at the He I D3 and we use the PCA inversion technique to derive their field strength, inclination and azimuth. All of the observed prominences are quiescent, as they were stable as filaments for at least three days and not eruptive. They present similar characteristics, they are highly dynamic and present horizontal magnetic fields. Statistically, the inclination from the local vertical is around 90 degrees, with some points around 60 and 120 degrees. The field strength is between 5 and 15 Gauss. We tested the effects of adding a turbulent field component to the horizontal field. For those pixels showing inclinations around 60 and 120 degrees, we find that such a model is compatible with the polarimetric observations. In some of these prominences, identified as "tornadoes" the field strength may reach 50 Gauss, and in the top of the tornadoes some points exhibit an inclination which cannot correspond to any model in our grid of models. We investigate different solutions.